Evaluation of the Inhibitory Potential of Casuarictin, an Ellagitannin Isolated from White Mangrove (Laguncularia racemosa) Leaves, on Snake Venom Secretory Phospholipase A2 - Rodrigues, Caroline Fabri Bittencourt [UNESP]; Ferreira, Marcelo José Pena; Belchor, Mariana Novo [UNESP]; Costa, Caroline R.C. [UNESP]; Novaes, Danielle P. [UNESP]; dos Santos, Adeilso Bispo [UNESP]; Tamayose, Cinthia I.; Pinho, Marcus Vinícius Terashima [UNESP]; de Oliveira, Marcos Antonio [UNESP]; Toyama, Marcos Hikari [UNESP] (MDPI, 2019)
Ellagitannins constitute the largest group of hydrolyzable tannins of plants, and, from this group, casuarictin (Casu) was identified in some plant species. However, to our knowledge, no investigation of secretory phospholipase A2 (sPLA2) inhibition by Casu has been performed yet. Casuarictin was isolated by chromatography n-butanol (n-BuOH) partition of Laguncularia racemosa leaves. The pharmacological and biological effects of Casu were evaluated on isolated sPLA2 from the rattlesnake (Crotalus durissus terrificus) and using a plant bacterial strain. The compound was able to form a protein complex consisting of a stable sPLA2 + Casu complex. Analyses carried out with matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF) revealed that the molecular mass of sPLA2 increased from 14,425.62 to 15,362.74 Da. The enzymatic activity of the sPLA2 + Casu complex was significantly lower than that of native sPLA2. Besides, molecular interactions of Casu with sPLA2 were able to virtually abolish the native edematogenic effect as well as myonecrosis induced by the protein when injected 10 min after sPLA2. Therefore, Casu may be considered a potential anti-inflammatory that can be used to treat edema and myonecrosis induced by serine-secreting phospholipase A2. In addition, the compound also showed great antimicrobial potential.
Keywords: Anti-inflammatory; Casuarictin; Crotalus durissus terrificus; Edema; Enzymatic inhibition; Laguncularia racemosa; Myonecrosis; Secretory phospholipase A2